Assessing Governance Frameworks for Effective Oversight of Upstream Petroleum Operations: Adopting Best Practices in Tanzania’s Sector Governance - Pastory Dickson; Allen Emmanuel Mrindoko (International Journal of Business, Economics, and Social Development, 2026)
Ineffective governance structures and regulatory practices have continued to affect transparency, accounts, and efficiency in Tanzania’s upstream petroleum sector, which makes the sector prone to risks associated with compliance and challenges in governance. The study aims to evaluate the impact of governance structures and best practices to the oversight of the country’s upstream petroleum sector. This study was guided by Agency Theory, which focuses on monitoring and accountabilities between regulators and operators, and Institutional Theory, which focuses on Legitimacy and Best Practices based on global standards. A cross-sectional research design and approach based on a quantitative strategy was used employed. 328-sample size were sought from various organizations in Tanzania. Semi-structured questionnaire instrument was used as data collection methods. GLM to control for regression was adopted for data analysis. The results show highly positive relationship between governance structures and oversight effectiveness in Tanzania’s upstream petroleum sector with ρ of 0.747, p < 0.01 and a highly positive relationship between Best Practices and oversight effectiveness in Tanzania’s upstream petroleum sector with ρ of 0.686, p < 0.01. GLM tests showed both governance structures (β = 0.512, p < 0.001) and Best Practices (β = 0.427, p < 0.001) have positive influences on oversight effectiveness in Tanzania’s upstream petroleum sector and explained a total joint percentage of 62%. Study concluded that effective governance structures and Best Practices have played a crucial role in oversight effectiveness in Tanzania’s upstream petroleum sector. It recommends the improvement of the regulatory clarity, coordination of institutions, engagement of stakeholders, capacity enhancement, and technology-enabled monitoring of sustainable upstream petroleum governance in Tanzania.